Laparoscopy for the Treatment of Congenital Hernia: Use of Surgical Meshes and Mesenchymal Stem Cells in a Clinically Relevant Animal Model - Marinaro, Federica; Casado, Javier G.; Blázquez, Rebeca; Brun, Mauricio Veloso; Marcos, Ricardo; Santos, Marta; Duque, Francisco Javier; López, Esther; Álvarez, Verónica; Usón, Alejandra; Sánchez-Margallo, Francisco Miguel (Frontiers in Pharmacology, 2020)
More than a century has passed since the first surgical mesh for hernia repair was developed, and to date, this method is still the most widely used regardless of the great number of complications it poses. The purpose of this study was to combine stem cell therapy and laparoscopy for the treatment of congenital hernia in a swine animal model. Porcine bone marrow-derived mesenchymal stem cells (MSCs) were seeded on polypropylene surgical meshes using a fibrin sealant solution as a vehicle. Meshes with (cell group) or without MSCs (control group) were implanted through laparoscopy in Large White pigs with congenital abdominal hernia after the approximation of hernia borders (implantation day). A successive laparoscopic biopsy of the mesh and its surrounding tissues was performed a week after implantation, and surgical meshes were excised a month after implantation. Ultrasonography was performed to measure hernia sizes. Flow cytometry, histological, and gene expression analyses of the biopsy and necropsy samples were performed. The fibrin sealant solution was easy to prepare and preserved the viability of MSCs in the surgical meshes. Ultrasonography demonstrated a significant reduction in hernia size 1 week after implantation in the cell group relative to that during the implantation day (p < 0.05). Flow cytometry of the mesh-infiltrated cells showed a non-significant increase of M2 macrophages when cell group was compared to control group 1 week after implantation. A significant decrease in the gene expression of VEGF and a significant increase in TNF expression were determined in the cell group 1 month after implantation compared to that of the control group (p < 0.05). Here, we propose an easy and feasible method to combine stem cell therapy and minimally invasive surgical techniques for hernia repair. In this study, stem cell therapy did not show a great immunomodulatory or regenerative effect in overcoming hernia-related complications. Only the use of a clinically relevant animal model with congenital hernia, such as the one of this study, can closely resemble the clinical human condition. Further research should use this valuable animal model to reduce the complications of hernia surgery with stem cell therapy.